KEMANDIRIAN FISKAL DAERAH OTONOMI: KESIAPAN DAERAH DALAM PELIMPAHAN KEWENANGAN PENGELOLAAN PAJAK BUMI DAN BANGUNAN PERKOTAAN DAN PERDESAAN - Lastria Nurtanzila (NATAPRAJA, 2016)
Financially independent for a region is a must in decentralization era. This article try to examine how central and local government push their effort to make a region financially independent. One of the policy agenda is to delegate the authority to manage property tax from central government to local government. Based on Law Number 28/ 2009, property tax becomes the authority of local government, this is a very good news to increasing local revenue. The increasing of local revenue is expected to increasing local government capacity to funding their activity. Nevertheless, local government readiness becomes a big issue, known that until 2013 only 123 kabupaten/kota that already implemented this policy, where the rest of the kabupaten/kota are still not ready to implement it. But, the current issue is the capacity of readiness, not all of the kabupaten/kota has the capicity and capability to implement the policy. Therefore, this policy needs to be reck by central government, so in the future this policy can be a good instrument to made region financially independent.Keywords: Financially Independent, Decentralization, and Property Tax